Resources to develop the research publication competencies of Russian researchers - N. G. Popova; E. I. Khabirova (Образование и наука)
Introduction. In the last decades, due to the increased number of international research collaborations, the role of auxiliary institutions which contribute to the development of research publication competencies has increased. Competencies are required for writing, preparing, publishing, and promoting scientific articles. The formation of such competencies is carried out at different levels of higher education as part of the current Federal State Educational Standard (FSES), including prorammes of additional professional education, as well as initiatives of auxiliary university departments and non-university organisations.Aim. This article aims to analyse the resources available for the development of research publication competencies in Russia in terms of the opportunities offered by different participants of the educational process.Methodology and research methods. The study compared and analysed open access regulatory documentation, reviewed and systematised data from the websites of auxiliary university departments and non-university organisations, and used data from in-depth interviews.Results. The article describes the prerequisites for the formation of research publication competencies in higher education in Russia. An overview of effective practices to develop such competencies is given, taking into account the national context and available higher education programmes. The article provides an overview of the functionality of auxiliary university departments and non-university organisations, whose activities support publication activity. The role of academic writing teachers, consultants, translators, editors, and reviewers in the development of the competencies of the authors of scientific publications is determined. The importance of the closer interaction of all participants in the publication process is substantiated: authors, translators, and editors of texts; and teachers of scientific writing courses with editors and reviewers of scientific journals.Scientific novelty. The scientific novelty of this article refers to a detailed description of the resources for the development of research publication competencies and their compliance with the requirements of the Federal State Educational Standard, which have not been investigated in such correlation before.Practical significance. The results can be used to develop a set of measures to systematise approaches to developing research publication competencies.